2013
DOI: 10.1002/zaac.201300321
|View full text |Cite
|
Sign up to set email alerts
|

On Ammonium‐bis(dithiocarbamato)‐copper(I)‐monohydrate and Mono(dithiocarbamato)‐copper(I)

Abstract: The title compounds NH 4 [Cu(S 2 CNH 2 ) 2 ]·H 2 O (A) and CuS 2 CNH 2 (B) were prepared from aqueous alcoholic solutions by reaction of ammoniumdithiocarbamate with copper sulfate in presence of excess cyanide as reductive. (A) crystallizes in the orthorhombic space group C222 1 (No. 20) with a = 8.9518(6), b = 9.6414(6) and c = 10.6176(8) Å, Z = 4. (B) crystallizes in the orthorhombic space group P2 1 2 1 2 1 (No. 19) with a = 5.9533(4), b = 6.6276(4) and c = 9.4834(5) Å, Z = 4. In the crystal structure of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The investigation of the intermediate (XRPD) obtained at T ≈ 170 °C revealed that appreciable amounts of the final product (Ag 2 S) is formed at relatively low temperature, yet before all of the starting phase is decomposed. The absence of AgSCN2123 as an intermediately formed compound is remarkable, which is in contrast to the homologue copper compound CuS 2 CNH 2 , where the corresponding thiocyanate CuSCN was detected as an intermediate compound 18. The thermal decomposition of AgSCN was investigated earlier,24,25 however not in inert gas atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the intermediate (XRPD) obtained at T ≈ 170 °C revealed that appreciable amounts of the final product (Ag 2 S) is formed at relatively low temperature, yet before all of the starting phase is decomposed. The absence of AgSCN2123 as an intermediately formed compound is remarkable, which is in contrast to the homologue copper compound CuS 2 CNH 2 , where the corresponding thiocyanate CuSCN was detected as an intermediate compound 18. The thermal decomposition of AgSCN was investigated earlier,24,25 however not in inert gas atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…They contain an icosahedral Cu12 core, two faces of which are capped, while the final copper atom is encapsulated as a linear [CuH2] − moiety (Figure 14b). [114]. Somewhat unexpectedly, however, the structure does not show the expected [Cu(S 2 CNH 2 ) 2 ] − anion, but rather is a coordination polymer in which each dithiocarbamate ligand spans two copper centres (Figure 15a).…”
Section: Copper(i) Dithiocarbamate Complexesmentioning
confidence: 91%
“…80-95 • C, a second coordination polymer [Cu(S 2 CNH 2 )] n results. While each copper remains bound to four dithiocarbamates, the CuS 4 tetrahedral are now linked in a 3D array reminiscent of a filled β-cristobalite structure [114].…”
Section: Copper(i) Dithiocarbamate Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium strong and very weak hydrogen bonds (N–H ··· S, Table 3) induce additional cohesion. Recently the closely related orthorhombic, filled β‐cristobalite like structure of the homologue copper compound CuS 2 CNH 2 was reported,18 where the distortion of the tetrahedra is clearly more pronounced.…”
Section: Resultsmentioning
confidence: 99%